1417Geographical differentials and trends in obesity burden in Argentina: a socio-demographic approach. (2nd September 2021) - Aballay, Laura Rosana; Baker, Julia Wirtz; Haluszka, Eugenia; Muñoz, Fabián Leonardo; Niclis, Camila; Pou, Sonia Alejandra
Abstract: Background: In Argentina, there is evidence suggesting the obesity prevalence follows a social gradient. We analyze geographical differentials and trends in obesity burden according to socio-demographic conditions in Argentina (2005-2013). Methods: The geographical distribution (n = 24 provinces) of the obesity burden in adult population of Argentina in 2005, 2009, and 2013 was analyzed by using mapping techniques. The National Survey of Chronic Diseases Risk Factors datasets were used to estimate and map the age-standardized prevalence of obesity (ASPO) and group-specific prevalence (% obesity) by province and year. Population groups were defined according to socio-demographic factors: age, sex, income level, education, and poverty level (by unsatisfied basic needs –UBN). Results: Most of the provinces had an increasing ASPO between 2005 and 2013. In 2013, 75% of the provinces showed an ASPO above 20% in men, while 50% of the provinces exceed this ASPO value in women. In both sexes, the middle-aged group presented the most unfavorable situation. Overall, all the socio-demographic groups considered showed growing trends in obesity prevalence, although there were geographical disparities. Among the middle-income level population, a marked rising change was observed from 2009 to 2013. The population with incomplete primary education presented higher prevalence for all the years studied compared to the population with university education. Conclusions: Since 2005, there was an overall increase in obesity prevalence in Argentina, with persistence of geographical disparities according to socio-demographical conditions. Key messages: An overall rising trend in obesity prevalence was observed in Argentina. Geographical disparities by social groups were observed.